Uji Homogenitas dan Stabilitas Bungkil Kedelai Sebagai Bahan Standar pada Pengujian Nutrien di Laboratorium Pakan: Assessing Homogeneity and Stability of Soybean Meal for Nutrient Testing Standards in Feed Laboratories - Dwinarto, Bondan; Laconi, E B; Jayanegara, A (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
One method for laboratories to achieve accreditation is through proficiency testing, which relies on the availability of reference materials from specialized providers or manufacturers. This research investigates the stability of both imported and locally sourced soybean meal, which serves as control samples in animal feed laboratories. The parameters assessed in this research include water content, ash content, and crude protein levels. Statistical analyses were conducted according to the proficiency testing guidelines outlined in SNI ISO 13528:2016, focusing on homogeneity and stability assessments. The results indicate that both local and imported soybean meals are homogeneous across the tested parameters. However, the stability tests reveal differing results: local soybean meal shows instability in water content and crude protein, while its ash content remains stable. In contrast, the imported soybean meal exhibits stable water and ash content but unstable crude protein levels. In conclusion, soybean meal can be utilized as a control sample in feed laboratories for short-term applications due to its susceptibility to changes in material characteristics. Key words: homogeneity, stability, soybean meal